Akurasi Analisis Time Series Dengan Metode Rmse Pada Forecasting Harga Saham Bank Syariah Yang Ada Di BEI - Hikmah Nur Yashinta; Agus Aklis; Fitria Berliana Sari; Mu'arifatin Nuril Ula (Universitas Muhammadiyah Sumatera Utara, 2022)
Objective: to determine the accuracy of time series analysis using the RMSE method used in forecasting the monthly stock price of BRIS on the IDX for 5 months. Findings: The results of the RMSE prediction accuracy were obtained with a total of 215,812. Results: From the calculation of RMSE data from January to May, the results obtained are: (1) January of 7,018, (2) February of 144,589, (3) March of 35,218, (4) April of 26,179, (5) May of 2,808 with a total of 215,812. then the total of the total share prices from January to May is entered into the RMSE formula by dividing the total by n (amount of data) so as to get a result of 207.7558. Implications: based on the results of the discussion of this study, the implication is that the accuracy of time series analysis combined using the RMSE method is very suitable for forecasting Islamic banking stock prices. If this forecast continues to be developed, investors will not have to worry about calculating the stock price of a company. So that investors and the general public can easily see the movement of a company's stock price.